2020
DOI: 10.1089/wound.2018.0924
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT Imaging: A Noninvasive Approach for Evaluating Serial Changes in Angiosome Foot Perfusion in Critical Limb Ischemia

Abstract: Objective: To investigate the feasibility of serial radiotracer-based imaging as a noninvasive approach for quantifying volumetric changes in microvascular perfusion within angiosomes of the foot following lower extremity revascularization in the setting of critical limb ischemia (CLI). Approach: A CLI patient with a nonhealing foot ulcer underwent singlephoton emission computed tomography (SPECT)/computed tomography (CT) imaging of the feet before and after balloon angioplasty of the superficial femoral arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Though doubts about the real clinical benefit of WDR for both bypass and EVT have been raised in contemporary literature 1-8, 10, 19-21, 32, 37 , using modern microcirculatory diagnostic methods with valuable topographic information 10,19,40,42 . While some authors have found the assessment of anatomical 6,10,16,28 and physiological 16,40,41 angiosomal flow by MRI oximetry 40 , trans-cutaneous laser Doppler 16,28 , or peripheral SPECT-Scan perfusion 10,[41][42][43] useful, others have questioned the utility of topographic reperfusion using white-light tissue spectrophotometry 44 , and low-frequency oscillations analyzed by diffuse speckle contrast analysis 45 . The clinical value of all these studies that support or refute specific postoperative angiosomal microcirculatory changes is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…Though doubts about the real clinical benefit of WDR for both bypass and EVT have been raised in contemporary literature 1-8, 10, 19-21, 32, 37 , using modern microcirculatory diagnostic methods with valuable topographic information 10,19,40,42 . While some authors have found the assessment of anatomical 6,10,16,28 and physiological 16,40,41 angiosomal flow by MRI oximetry 40 , trans-cutaneous laser Doppler 16,28 , or peripheral SPECT-Scan perfusion 10,[41][42][43] useful, others have questioned the utility of topographic reperfusion using white-light tissue spectrophotometry 44 , and low-frequency oscillations analyzed by diffuse speckle contrast analysis 45 . The clinical value of all these studies that support or refute specific postoperative angiosomal microcirculatory changes is indisputable.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the analysis of Pearson's correlation coefficient also does not fully support to the foot angiosome concept. To date, regarding the angiosome concept, some studies have focused on assessment of peripheral tissue perfusion to identify the origin location of diabetic foot ulcers with bench-top optical modalities [29][30][31][32][33][34] , to evaluate the quantitative wound healing with high-resolution imaging modalities such as CT 35,36 , SPECT/CT 37,38 and MRI perfusion [39][40][41] , and to evaluate leg revascularization surgeries Table 6. Comparison of ranks between six cross-correlations and six Pearson's correlation (CORR) coefficients at zero lag and in supine posture according to baseline and release periods from one subject's foot.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, SPECT/CT imaging with technetium-99m ( 99m Tc)-tetrofosmin, a standard myocardial perfusion radionuclide that is retained based on mitochondrial membrane potential and tissue viability ( 18 ), has been shown to allow for evaluation of relative perfusion defects within specific vascular territories, or angiosomes, of the feet ( 19 ). Additionally, this approach has revealed utility for detecting resting differences in regional foot perfusion between CLI patients and healthy control subjects ( 19 ), assessing tissue viability that corresponds with the subsequent level of amputation ( 20 ), and quantifying regional improvements in relative perfusion within the foot that occurs in response to endovascular revascularization ( 21 , 22 ). Most recently and importantly, perfusion imaging of the feet using SPECT/CT imaging has also demonstrated prognostic value for predicting risk for lower extremity amputation in patients with CLI who underwent endovascular revascularization for limb salvage, where patients who were high perfusion responders to revascularization experienced greater limb salvage success compared to those who were categorized as low perfusion responders ( Figure 1 ) ( 22 ).…”
Section: Imaging Of Lower Extremity Skeletal Muscle Perfusionmentioning
confidence: 99%